Organic acid adsorption and mineralization in oxisols with different textures - Andrade,Felipe Vaz (2013)
Organic acids play an important role in the nutritional conditions of plants. Their relevance is related to their formation dynamics, mineralization rate and adsorption by soil colloids. This study was carried out to evaluate the dynamics of mineralization and adsorption of organic acid (acetic acid - AA, citric acid - CA and humic acid - HA) applied to the soil. Samples of two Oxisols were used: Rhodic Haplustox (LV) and Typic Haplustox (LVA). The mineralization experiment was arranged in a 2 x 3 x 5 factorial design, based on the factors: two soils (LV and LVA) x three organic acid (OA) types (AA, CA and HA) x five OA rates (0, 1, 2, 4, and 8 mmol dm-3). Organic carbon mineralization in samples was measured by the C-CO2 efflux, produced by the microbial activity, in a 30-day (measurements after 4, 8, 12, 21, and 30 days) and in a 4-day experiment (measured after 24, 48, 72 and 96 h). Organic acid adsorption was tested in a 2 x 2 x 5 x 4 factorial design, with the factors and levels: two Oxisols; two organic acids (AA and CA); five OA rates (0, 1, 2, 4, and 8 mmol dm-3) and four adsorption periods (6, 24, 48, and 72 h). The C-CO2 production of soil treated with CA was highest. In the adsorption experiment, the affinity of CA to soil adsorption sites was greatest. The adsorption of organic acids to soils may be an important mechanism by which bioavailability and thus mineralization capacity by microbial activity are reduced.